Seasonal changes in physical capacities of basketball players according to competitive levels and individual responses - Ferioli, D.; Bosio, A.; Zois, J.; La Torre, A.; Rampinini, E. (PLOS ONE, 2020)
Purpose: The aim of this study was to quantify changes in physical capacities of thirty-eight basketball players selected from different teams, as well as from varying competitive levels (i.e. Division I, Division II and Division III) during the preparation and in-season periods. Methods: Pre (T1) and post (T2) preparation period and during regular season (T3), the players completed a Yo-Yo Intermittent Recovery test—level 1. Following a 3 to 8 days-break, players performed a 6-min continuous running test (Mognoni`s test), a counter-movement jump test and a 5-min high-intensity intermittent running test. Results: Blood lactate concentration measured after the Mognoni`s test was significantly reduced from T1 to T2, and from T2 to T3 (P<0.001, Eta2 = 0.424). The distance covered during the Yo-Yo Intermittent Recovery test was significantly increased only from T1 to T2 in Division II and III (P<0.001, Eta2 = 0.789). Similarly, the physiological responses to high-intensity intermittent running test were improved only from T1 to T2 (all P<0.001, ?2 = 0.495 to 0.652). Despite significant changes observed in running tests from T1 to T2, at individual level 35-55% of players did not show a very likely improvement. Relative peak power produced during vertical jumps at T3 by Division I players was increased compared to T1 (ANOVA interaction, P = 0.037, ?2 = 0.134). Conclusins: The main improvements in physical capacities occurred during the preparation period, when the aerobic fitness and the ability to sustain high-intensity intermittent efforts were moderately-to-largely improved. However, it appears that the preparation period does not consistently impact on vertical jump variables. Aerobic fitness and force/power production during vertical jumps appear to improve across the competitive season (slightly-to-moderately). Physical tests should be used to identify weaknesses in physical performance of players and to monitor their fatigue status, with the aim to develop individualized training programs.